If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(u + 3) = -2(4u + -1) + 2u Reorder the terms: 6(3 + u) = -2(4u + -1) + 2u (3 * 6 + u * 6) = -2(4u + -1) + 2u (18 + 6u) = -2(4u + -1) + 2u Reorder the terms: 18 + 6u = -2(-1 + 4u) + 2u 18 + 6u = (-1 * -2 + 4u * -2) + 2u 18 + 6u = (2 + -8u) + 2u Combine like terms: -8u + 2u = -6u 18 + 6u = 2 + -6u Solving 18 + 6u = 2 + -6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '6u' to each side of the equation. 18 + 6u + 6u = 2 + -6u + 6u Combine like terms: 6u + 6u = 12u 18 + 12u = 2 + -6u + 6u Combine like terms: -6u + 6u = 0 18 + 12u = 2 + 0 18 + 12u = 2 Add '-18' to each side of the equation. 18 + -18 + 12u = 2 + -18 Combine like terms: 18 + -18 = 0 0 + 12u = 2 + -18 12u = 2 + -18 Combine like terms: 2 + -18 = -16 12u = -16 Divide each side by '12'. u = -1.333333333 Simplifying u = -1.333333333
| 4x-3=20x+3 | | 0=4.9x^2+5x-1.6 | | 7x-(6x+7)=2x-14 | | 5w+1-2(-7w-7)=3(w-1) | | 103=31+8x | | 201=-9k+66 | | f(x)=4x^2-6x+3 | | -4z=8z-5 | | 5×1/8 | | q^2+14q+49=0 | | 4[-x-7]=-1 | | x+(x+1)=(x+2)*(x+2)-10 | | -27=8x+21 | | n/-3-7=14 | | (2x)+7=(2x) | | -3(5w-2)+7w=2+2(3w-3) | | 7v/4=35 | | (x)+(7x-12)=180 | | ((3/4)*x^-1*y)^-2 | | x^2-98=x^2-10 | | 14a+2a-15a=a | | 4*4x+4*-5=2 | | x+8.2=-5.8 | | 5(5x+2)=45 | | 8x+6y=186 | | f(x+1)=3x^2+4x-4 | | X/4=x/5=-13 | | -f(x)=3x^2+4x-4 | | 6w^2=96 | | c=200+0.67y | | -5.8+8.2=2.4 | | 7x-4=2+6x |